2021
DOI: 10.3389/fphar.2021.704205
|View full text |Cite
|
Sign up to set email alerts
|

The Drug Repurposing for COVID-19 Clinical Trials Provide Very Effective Therapeutic Combinations: Lessons Learned From Major Clinical Studies

Abstract: SARS-CoV-2 has spread across the globe in no time. In the beginning, people suffered due to the absence of efficacious drugs required to treat severely ill patients. Nevertheless, still, there are no established therapeutic molecules against the SARS-CoV-2. Therefore, repurposing of the drugs started against SARS-CoV-2, due to which several drugs were approved for the treatment of COVID-19 patients. This paper reviewed the treatment regime for COVID-19 through drug repurposing from December 8, 2019 (the day wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 131 publications
(144 reference statements)
0
90
0
Order By: Relevance
“…Some large clinical trials with most patients are ACTT-1, ACTT-2, and RECOVERY trials. These trials results showed the best therapeutic option, such as remdesivir or its combination with different antibodies (259). All the chemical components based therapeutic molecules have been developed using the drug targets, especially the primary drug target proteins of the virus or the host (262).…”
Section: The Strategy and Insight In Vaccine Design Mabs Development ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some large clinical trials with most patients are ACTT-1, ACTT-2, and RECOVERY trials. These trials results showed the best therapeutic option, such as remdesivir or its combination with different antibodies (259). All the chemical components based therapeutic molecules have been developed using the drug targets, especially the primary drug target proteins of the virus or the host (262).…”
Section: The Strategy and Insight In Vaccine Design Mabs Development ...mentioning
confidence: 99%
“…Several small molecule-based therapeutics have been approved for the treatment of COVID-19. In these cases, therapeutic development strategies have mainly been used to repurpose drugs (247,(259)(260)(261). Several clinical trials have been performed from small-size to large-size depending on the number of COVID-19 patients to understand the effectiveness of repurposing drugs.…”
Section: The Strategy and Insight In Vaccine Design Mabs Development ...mentioning
confidence: 99%
“…HSCT patients are known to be highly immunocompromised due to past chemotherapy or immunosuppressive agents for graft-versus-host disease (GVHD). Prevention of COVID-19 is therefore critically important in these patients, while some treatments, including immunotherapy, are considered to be promising strategies against COVID-19 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This creates a lag in the productivity of pharmaceutical research to develop a new drug, resulting in a persistent gap between therapeutic needs and available treatments. Despite base evidence being of variable quality, existing drugs have been repurposed in the war against the coronavirus pandemic [11]. Even though vaccines have been made available for the general populace, there is no specific treatment for the patients suffering from the disease.…”
Section: Introductionmentioning
confidence: 99%